الآليات القانونية لجذب الاستثمار الأجنبي المباشر في ظل القانون 18 - 22 - زهرة شريك (جامعة المسيلة, 2025)
Foreign investment is considered one of the most effective. Ways of achieving development in all fields ، especially economic and Social. Since its independence until now Algeria has focused one this aspect and has included Strategies the attraction of foreign direct investment through the many guarantees and incentives provided by the new investment law of 18.22، which can be considered a qualitative leap in the field of investment، given that it attracts foreign investors to establish their investment projects with ease by Seeking to provide an appropriate investment climate، we also hope to develop these legal mechanisms in a way that ensures the achievement of the desired of the form.
Keywords: Foreign investment- guarantees-incentives- investment law-investment climate- legal mechanisms .